2014
DOI: 10.5539/hes.v4n1p18
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Eportfolios in Finance Studies: A Cross-Country Study

Abstract: This study explores the use of ePortfolios as an efficient assessment tool to support students pursuing a Business degree, where Finance is a major component. We conducted an analysis on the role of ePortfolios in Higher Education at Dublin Institute of Technology (Republic of Ireland) and at Universitat Jaume I (Spain) for undergraduate studies. Our findings suggest that ePortfolios could be used to facilitate and enhance students self-regulated learning experiences where the role of the instructor is fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…This finding confirms Penny Light et al (2012) and Eynon & Gambino's (2017) theories that eportfolio based learning can develop students' critical thinking skills. Further, it is in keeping with previous research carried out by Nguyen & Ikeda (2015), Morales et al (2016) Dominguez et al (2014) who found that learning with an eportfolio, supported the development of self-regulation in higher education students. However, there are no previous empirical studies which have examined the relationship between critical thinking skills development, and eportfolio based learning.…”
Section: Discussionsupporting
confidence: 91%
“…This finding confirms Penny Light et al (2012) and Eynon & Gambino's (2017) theories that eportfolio based learning can develop students' critical thinking skills. Further, it is in keeping with previous research carried out by Nguyen & Ikeda (2015), Morales et al (2016) Dominguez et al (2014) who found that learning with an eportfolio, supported the development of self-regulation in higher education students. However, there are no previous empirical studies which have examined the relationship between critical thinking skills development, and eportfolio based learning.…”
Section: Discussionsupporting
confidence: 91%